TINJAUAN MANAJEMEN SUMBER DAYA INSANI (MSDI) PADA SISTEM REKRUTMEN KARYAWAN DI BANK SYARIAH INDONESIA (BSI) GADAI EMAS BANGKALAN - Jantan Ari Sadewo; Dzikrulloh Dzikrulloh (LP2M IAI Miftahul Ulum Pamekasan, 2023)
The current development of Islamic banking has a logical consequence of increasing the demand for labor. The development of human resources has become a necessity due in part to the pace of development of sharia-based industries, especially the financial institution industry. The purpose of writing this article is to describe how the employee recruitment process is at BSI Gadai Emas Bangkalan and will later be reviewed using the theory of Human Resource Management (MSDI) in Islamic economics. In this study the authors used MSDI theory as a basis which included basic understanding, MSDI principles, MSDI processes, and determinants of MSDI. The research method used is a qualitative approach with a descriptive research type, data collection methods using interviews and documentation, data analysis methods using descriptive qualitative analysis. The results showed that in BSI before the open recruitment process had implemented good planning/attakhthiith related to employees, organizing/attanziem already existed and was running optimally, directing (actuating/at-TANzieq) was commanded by the leader, the leader has implemented a leadership spirit that emphasizes Islamic family principles, and control (controlling/almuraqabah) is carried out in a good system supported by constructive policies. For the recruitment system, namely the dissemination of information, selection, acceptance, training, division of jobs or sections, determination of salary and rewards, and finally related to attendance and discipline while working. So the recruitment system above is in accordance with the process in MSDI.